2007
DOI: 10.2169/internalmedicine.46.1690
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Renal Amyloidosis:A Clinicopathological Study Using Cluster Analysis

Abstract: Objective There is no standardized therapy for renal amyloidosis, which shows rapid progression and poor prognosis. Here, we used

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
1
17
1
Order By: Relevance
“…The damage in the tubular basement membrane and interstitium was evaluated using the point-counting method. 19 Under high magnification (400×) with an 81-point (100-square) eyepiece micrometer, we analyzed at least 10 consecutive and nonoverlapping cortical fields from each biopsy section. The points overlying damaged regions in the tubular basement membrane and interstitial space were counted and included in the area percent of damage [tubulointerstitial (TI) damage].…”
Section: Histopathology Of the Kidneymentioning
confidence: 99%
See 1 more Smart Citation
“…The damage in the tubular basement membrane and interstitium was evaluated using the point-counting method. 19 Under high magnification (400×) with an 81-point (100-square) eyepiece micrometer, we analyzed at least 10 consecutive and nonoverlapping cortical fields from each biopsy section. The points overlying damaged regions in the tubular basement membrane and interstitial space were counted and included in the area percent of damage [tubulointerstitial (TI) damage].…”
Section: Histopathology Of the Kidneymentioning
confidence: 99%
“…These patients were divided into four groups with regard to renal prognosis and survival. 19 For each group, the following parameters were reviewed at the time of the biopsy as possible candidates for factors that are related to the cluster group showing severe anemia: sex, body mass index [BMI; body weight/(body height) 2 (kg/m 2 )], age (years), systolic blood pressure (BP) (mmHg), diastolic BP (mmHg), duration after the diagnosis of DM (months), serum levels of albumin (mg/dL), blood urea nitrogen (BUN) concentrations (mg/dL), SCr concentrations (mg/dL), the estimated glomerular filtration rate [eGFR (mL/min/·1.73 m 2 )] that was validated in the Japanese population, 20 iron (Fe) levels (µg/dL), total cholesterol levels (mg/dL), triglyceride levels (mg/dL), fasting blood sugar levels (mg/dL), HbA1c (%) levels, urinary protein secretion (g/day), KW nodules, DGS index, and TI grade of damage (0 to +3).…”
Section: Histopathology Of the Kidneymentioning
confidence: 99%
“…2,3 Renal involvement is very common in FMF-related SA, which is thus a prevalent cause of both microand macroproteinuria and chronic kidney disease (CKD) in this geographic region. [2][3][4] Regardless of primary cause, patients with CKD as a result of SA have an even poorer outcome than other CKD patients. [5][6][7] Although the exact causes for this is are not known, it has been suggested that SA itself is a cause of cardiovascular disease (CVD).…”
mentioning
confidence: 99%
“…Bohle, et al reported that tubulointestinal damage in renal amyloidosis, and especially fibrosis, is an important determination of renal prognosis 8,9) . The rate of progression to renal failure is usually slow, but depends directly on the intensity of proteinuria and extension of amyloid deposits, especially in the vessels and tubules 10) .…”
Section: Discussionmentioning
confidence: 99%